Donor-derived Cell-free DNA Complements De Novo Class II DSA in Detecting Late Alloimmune Injury Post Kidney Transplantation. Issue 2 (26th January 2022) - Butiu, Maria; Obrisca, Bogdan; Sibulesky, Lena; Bakthavatsalam, Ramasamy; Smith, Kelly D.; Gimferrer, Idoia; Warner, Paul; Ismail, Gener; Leca, Nicolae
Abstract : Background: We sought to evaluate the association between de novo donor-specific antibodies (dnDSAs) class and their mean fluorescence intensity (MFI) with donor-derived cell-free DNA (dd-cfDNA), aiming to further clarify the biomarker utility of these noninvasive tests in relation to renal allograft function and histology. Methods: The study included kidney transplant recipients (n = 171) who underwent surveillance testing with DSA and dd-cfDNA as part of their clinical care between September 2017 and December 2019 at our center. Results: We identified dnDSA in 43 patients (25%) at a median of 4.63 y (IQR, 1.5–7) posttransplant. The presence of DSA with MFI >2500 was associated with a median dd-cfDNA of 0.96% (IQR, 0.26–2.95) significantly higher than in patients with DSA MFI <2500 (0.28%; IQR, 0.19–0.39) or without detectable DSA (0.22%; IQR, 0.17–0.37; P < 0.001). Class II dnDSAs were the most prevalent dnDSA (88.3%), the majority with MFI >2500 (82.9%). Patients with DQ-dnDSAs (47.4%) had higher MFI and dd-cfDNA levels than other class II dnDSAs. By comparison, all patients that developed only class I DSAs had MFI <2500 and a low dd-cfDNA. In addition, the serum creatinine was 1.55 ± 0.48 mg/dL in those dnDSA-negative, 1.15 ± 0.37 mg/dL in those with dnDSA MFI <2500, and 1.53 ± 0.66 mg/dL in those with dnDSA MFI >2500 ( P = 0.05). After multivariate adjustment, an elevated dd-cfDNA was independently associated with the presence of dnDSA with MFI ≥2500. We identified that both dd-cfDNA and dnDSAs were strongly associated with antibody-mediated rejection, whereas for individual Banff histological lesions, DSA MFIs ≥2500 had the strongest association with C4d staining score and dd-cfDNA >1% with microvascular inflammation. Conclusions: Our study identifies class II dnDSA as being strongly associated with late alloimmune injury post kidney transplant independent of allograft dysfunction and shows that dd-cfDNA may complement the clinical significance of dnDSAs.